Stock Market Dynamics and Real Estate Sector Performance in Nigeria: Evidence from Secondary Data - Abdulkadir, Misbahu Falaki; Gwarmai, Ja’afar Garba Ya’u; Milala, Sani Inusa (PT.KARYA GEMAH RIPAH, 2025)
performance of Nigeria’s real estate sector has increasingly been shaped by fluctuations in the stock market and macroeconomic conditions. Despite its potential as a driver of economic growth, the sector remains vulnerable to market volatility, inflationary pressures, and limited capital market participation. This study examines the relationship between stock market dynamics and real estate sector performance in Nigeria from 2009 to 2023, considering the roles of inflation and interest rates. A quantitative research design was adopted using secondary annual data obtained from the Nigerian Exchange Group and the Central Bank of Nigeria. Stock market dynamics were proxied by the All-Share Index (ASI) and market capitalization, while real estate performance was measured by the NGX Real Estate Index. Data analysis using Stata involved descriptive statistics, correlation analysis, and regression modeling. The results indicate that both the ASI (? = 0.0023, p < 0.01) and market capitalization (? = 0.0040, p < 0.01) exerted positive and statistically significant effects on real estate sector performance. Inflation had a negative and marginally significant effect (? = ?0.6603, p ? 0.053), whereas interest rates were insignificant (? = 0.4832, p = 0.417). The model’s R² value of 0.987 suggests that 98.7% of variations in the Real Estate Index were explained by the selected variables. Overall, the findings establish that stock market dynamics are critical determinants of real estate sector performance in Nigeria, highlighting the need for strengthened capital market development and policies that enhance macroeconomic stability and support listed real estate firms.